Haptic search asymmetry does not occur due to different-shaped tactile symbols on capsule paper - Kento Imori; Tetsuya Watanabe (i-Perception, 2024)
Previous research on haptic search using sandpaper with different roughness levels as a target and distractors showed that rough sandpaper among fine “pops out” and can be searched for in a shorter time than when the roles of the target and distractors are reversed. However, it is not clear whether the same search asymmetry occurs with differences in the shapes of tactile symbols on capsule paper. To explore this possibility, we conducted a haptic search experiment using circles with or without a dot on capsule paper as a target and distractors, which are often used as point symbols in tactile maps for the blind. Contrary to our expectations, haptic search asymmetry did not occur between these two tactile symbols. Regardless of target type, the search times increased in proportion to the number of items (distractors plus target), as participants tended to adopt serial search strategy in which they placed their index or middle finger on the tactile symbol to distinguish it every time they found a new one. The ratio of the search times for target-absent to target-present trials is precise alignment with the occurrence rate of repetitive search trials.